A checklist of beetles (Insecta, Coleoptera) on pig carcasses in the suburban area of southwestern China: A preliminary study and its forensic relevance. (July 2016) - Lyu, Zhou; Wan, Li-hua; Yang, Yong-qiang; Tang, Rui; Xu, Lyu-zi
Abstract: Examining the succession pattern of carrion insects on vertebrate carcasses is widely accepted as an effective method to estimate the postmortem interval (PMI) of decayed bodies. Investigation of the community of sarcosaprophagous insects, especially flies and beetles, is the foundation of the succession pattern study. This study aimed to investigate the sarcosaprophagous beetles succession on animal carcasses in the suburban area of southwestern China and to establish a basic catalog for forensic application. The present study was conducted in 2013 in a mountain in Chongqing municipality with modified Schoenly traps. Carcasses of miniature pig were used to simulate human bodies. For most carcasses, five decomposition stages were observed. A total of 2108 adult coleopterans belonging to at least 61 species and 18 families were collected in the study, and most of the specimens occurred at the advanced decay stage. Omosita colon (Linnaeus, 1758), Necrodes nigricornis (Harold, 1875), Necrobia ruficollis (Fabricius, 1775) and Neosilusa ceylonica (Kraatz, 1857) were the dominant species. Highlights: The first study of sarcosaprophagous coleopteran community in southwestern China. The first study used Schoenly trap in forensic entomology research in East Asia. Intermittent rainfall could accelerate the process of adipocere formation of carcasses and further retard decomposition. Nitidulidae was observed as the only coleopteran species which could break down the adipocere slowly in this study.